2015
DOI: 10.3892/or.2015.4202
|View full text |Cite
|
Sign up to set email alerts
|

HAX-1 inhibits apoptosis in prostate cancer through the suppression of caspase-9 activation

Abstract: HS1 associated protein X-1 (HAX-1), a substrate of Src family tyrosine kinases, plays a critical role in cell apoptosis. However, its functions in prostate cancer remains unclear. The present study explored the role and mechanism of HAX-1 in cancer cell apoptosis. The mRNA and protein levels of HAX-1 in the prostate cancer cell lines PC-3, VCaP and DU145 were assessed. Cell proliferation, apoptosis and caspase-9 activities were assessed in DU145 after HAX-1 siRNA treatment. The mRNA and protein levels of HAX-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Overexpression of HAX-1 inhibits mitochondria collapse and subsequent release of mitochondria-sourced apoptotic molecules (such as cytochrome c). Therefore, HAX-1 protects the cancer cells from drug-initiated apoptotic signaling [3133]. In this study, we found that enforced expression of miR-125a promoted cisplatin-induced cell death by decreasing HAX- 1 expression directly.…”
Section: Discussionmentioning
confidence: 68%
“…Overexpression of HAX-1 inhibits mitochondria collapse and subsequent release of mitochondria-sourced apoptotic molecules (such as cytochrome c). Therefore, HAX-1 protects the cancer cells from drug-initiated apoptotic signaling [3133]. In this study, we found that enforced expression of miR-125a promoted cisplatin-induced cell death by decreasing HAX- 1 expression directly.…”
Section: Discussionmentioning
confidence: 68%
“…Upon apoptotic stimuli, some caspase-9 is discovered to move to the mitochondria and co-localized with HAX-1 [46]. Recent study also displayed that apoptosis in prostate cancer is suppressed by inhibition of caspase-9 [47]. Thus, HAX-1 is an anti-apoptotic molecule through inhibiting caspase-9 in some special cells.…”
Section: Endogenous Regulators Of Caspase-9mentioning
confidence: 99%
“…Caspase-9, a protein mainly localized in mitochondria, is a critical regulatory player in mitochondria-mediated apoptosis pathway. Activated caspase-9 cleaves and activates caspase-7 and -3 directly, leading to the biochemical destruction of the cells [31]. Bax is one of the pro-apoptotic genes, the overexpression of which results in apoptosis in a number of cells [32].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%